BAGALUIK - Medrian, Farli; Erfan, Erfan (FBS Universitas Negeri Padang, 2019)
AbstractThis article aimed to reshaping something exist became somthing complete, interesting and the new presentation. The idea of this work is sourced from repertoire of Talempong Unggan art tradition in Â Â Sumpur Kudus, Sijunjung Sub Disctirct, West Sumatera. The implementation of the work presented of processing the rythym and melody patterns of some elements of garap technique such as Unisono, canon, hocketing, interlocking, matrik, call and respon, by using these tones as follows, D +30, E+20, Fis-20, G, As+20. The music of Bagaluik was worked in a new form by cultivatingÂ the new rythym and melody patterns which existed in Talempong Unggan Tupai Bagaluik into several music intruments which were proposed by the composer. The performance of this music composition developed and mixed between rythym and melody patterns into some music instruments. This work was played by nine players they were, two players for talempong, one player for canang, two players for pianika, two players for gandang kantindiak, one player for aguang and one player for gitar bass.Keywords: Talempong Unggan, Bagaluik